Shake it or light it! The effects of cueing in desktop‐VR learning environments on search time and learning. - Decker, Daniela; Merkt, Martin (Journal of Computer Assisted Learning, 2024)
Background: Virtual reality (VR) offers much potential for learning, but it challenges learners' orientation. Objectives: This paper investigates whether it is possible to use light or movement cues to facilitate orientation in a search task in a desktop‐VR environment so that participants can better attend to the learning content presented simultaneously. Methods: In two pre‐registered online experiments, we investigated the effects of cueing (light and movement) on search time, learning, and several evaluation variables. Participants were asked to find tools in a virtual workshop, while information about the respective tool was narrated. Experiment 1 (N = 60) used a within‐subject design, that is, the objects were alternately highlighted by light, movement or not. For Experiment 2 (N = 159) the narration was substantially shortened, and a between‐subject design was used. Cognitive load and presence were measured additionally. Results and conclusions: In Experiment 1, only the movement cue decreased search time, indicating automatic guidance of learners' attention. There was no effect of cueing on learning, which may be due to the average search time being substantially shorter than the narration, leaving sufficient time to attend to the narration exclusively. In Experiment 2 search times were significantly faster for both cueing methods, but only the light cue resulted in better learning outcomes, which could be explained by the slightly lower presence in the movement cue condition. Implications: Results imply that it is important to develop cues that automatically guide attention without reducing presence. Lay Description: What is already known about this topic: Virtual reality (VR) offers a lot of opportunities for the integration of educational scenarios.VR is challenging for learners with regard to orientation in a 360° environment.Regarding learning outcomes, research on the effects of cues to highlight important content in a 360° environment is still rare.Presence, defined as the feeling of being there in a VR environment, is an important prerequisite for learning in VR. What this paper adds: The influence of light and movement cues on search times and learning outcomes in a desktop‐VR environment was tested.Movement cues can reliably reduce search times (indicating successful orientation), whereas light cues only reduced search times in predictable scenarios.In a predictable scenario, light cues enhanced learning outcomes compared with movement cues.Movement cues reduced presence, which is one potential reason why movement cues did not improve learning. Implications for practice and/or policy: Using light cues might assist orientation and enhance overall performance in predictable scenarios (i.e., when learners know what kind of cue to expect).In an unpredictable setting with variable cues, light cues did not facilitate orientation, whereas movement cues did.However, movement cues reduced presence, which may have negatively affected learning outcomes. It is important to develop cueing methods that also work in more unpredictable settings, but that do not reduce presence.